Drug-eluting stents in large coronary vessels improve both safety and efficacy compared with bare-metal stents in women: a pooled analysis of the BASKET-PROVE I and II trials. Issue 1 (14th May 2019) - Bjerking, Louise Hougesen; Hansen, Kim Wadt; Sørensen, Rikke; Prescott, Eva; Biering-Sørensen, Tor; Jeger, Raban; Kaiser, Christoph; Pfisterer, Matthias; Galatius, Søren
Abstract : Background: Drug-eluting stents (DES) have proven superior to bare-metal stents (BMS) in terms of safety and efficacy. However, inference to the female subgroup has been limited by low enrolment rates of women in clinical trials. The objective of this study was to investigate the safety and efficacy of DES versus BMS in women and men. Methods: In a pooled analysis of two all-comers randomised trials (Basel Stent Kosten-Effektivitäts Trial–Prospective Validation Examination (BASKET-PROVE) and BASKET-PROVE II) (n=4605), we examined safety and efficacy of DES versus BMS according to sex. Patients were followed 2 years for a composite endpoint of cardiac death, non-fatal myocardial infarction (MI) and clinically driven target-vessel revascularisation not related to MI. Results: Among the 1076 women and 3529 men included in the analysis, 65.6% of the women and 67.2% of the men were randomised to receive DES. At baseline, men had more complex coronary artery disease than women. After 2 years, DES reduced rates of major adverse cardiac events (MACE) compared with BMS in both women (cumulative incidence, 6.1% vs 14.7%; adjusted HR 0.36 (95% CI 0.24 to 0.54)) and men (7.7 vs 12.1%, HR 0.62 (0.50 to 0.77)), although the reduction in MACE rates was more pronounced in women (adjusted p=0.02 for sex-stent interaction). Event rates were lower in DES for both safety and efficacy outcomes, with the largest effect seen for non-MI TVR, in both women (2.3 vs 9.2%, adjusted HR 0.24 (0.13 to 0.44)) and men (4.0 vs 7.8%, adjusted HR 0.48 (0.36 to 0.64)) (adjusted p=0.049 for sex-stent interaction). Conclusions: In patients requiring stenting of large coronary arteries, DES were associated with improved safety in women and superior efficacy in both sexes as compared with BMS.